Developing A Framework For The Training Of Communication Skills In English For Institutional Drivers - Anie, Anie; Shamsudin, Sarimah; Lateh, Nor Hazwani Munirah (Universiti Sains Malaysia, 2016)

(untitled)
Communication skills development of institutional drivers from English for Specific Purposes perspective has been found inadequate as there are gaps which have not been satisfactorily addressed. In contrast, communication skills development from a human capital development perspective has been found to be systematically organised using a Training Needs Analysis (TNA) approach along three lines of analysis, i.e., Organisation, Task and Person (OTP). With that OTP typology we propose to develop a framework for development of communication skills in English for institutional drivers. Both qualitative and quantitative methods will be adopted for data collection. The qualitative data will be collected through interviews of top administrators, academic staff, non-academic staff, visiting professors and students. Additional data will be gathered through client appraisal forms, diary entries, observation and document analysis. The quantitative data will be gathered through survey questionnaires distributed to related respondents including, academic staff, non-academic staff, students and visitors. The qualitative data will be analysed using constant comparative method and Nvivo software while the quantitative data using SPSS version 20 involving descriptive and inferential descriptive statistics. Results of the analyses are used to develop a framework for the development of communication skills in English that has evaluated the training needs and expectations revealed at the Organisation, Task and Person levels. The study is significant in that it considers an alternative approach to development of the communication skills of the non-academic staff that meets the need for a more efficient and effective communication skills training programme.